2009
DOI: 10.1287/mnsc.1090.1045
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for Retailer Forecasting: Rebates vs. Returns

Abstract: T his paper studies a manufacturer that sells to a newsvendor retailer who can improve the quality of her demand information by exerting costly forecasting effort. In such a setting, contracts play two roles: providing incentives to influence the retailer's forecasting decision and eliciting information obtained by forecasting to inform production decisions. We focus on two forms of contracts that are widely used in such settings and are mirror images of one another: a rebates contract, which compensates the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 20 publications
0
53
0
Order By: Relevance
“…The sequence of contract offer and forecast investment we use in this paper is commonly used in models of supply chain contracting with demand forecast investments (Lariviere 2002, Taylor andXiao 2009). Note that retailers' demand forecasting might also come earlier than the supplier's contract offer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of contract offer and forecast investment we use in this paper is commonly used in models of supply chain contracting with demand forecast investments (Lariviere 2002, Taylor andXiao 2009). Note that retailers' demand forecasting might also come earlier than the supplier's contract offer.…”
Section: Discussionmentioning
confidence: 99%
“…1592-1610 screen retailers who are efficient forecasters. Taylor and Xiao (2009) show that under rebate contracts in a single supplier/single retailer setting, the retailer might overinvest in demand forecasting, and the system can benefit from the retailer having an inferior forecasting technology. Furthermore, a return contract instead of a rebate contract can coordinate the supply chain in this model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the retailer is a strong forecaster, the manufacturer would 5 Further, we observed that for every fixed value of 0 and c the difference between the integrated system profit and the decentralized total system profit I − M + R is first increasing and then decreasing as the retailer's forecasting accuracy parameter a increases in a ∈ 0 1 Thus, the gain in system profit from centralization I − M + R is largest when the retailer's forecasting accuracy is moderate. 6 See Taylor and Xiao (2009) and Shin and Tunca (2010) for analyses that formally model a retailer's forecasting effort decision.…”
Section: Numerical Studymentioning
confidence: 99%
“…Broadly speaking, the impact of information asymmetry is studied in the principal-agent framework in which the agent possesses private information that the principal attempts to elicit, and it has been applied in various areas to design optimal mechanisms, including nonlinear pricing [27], managerial compensation schemes [3], supply chain contracting [2,10,26]), and auctions [9,15,[28][29][30]. In strict contrast with the aforementioned papers, our setting exhibits a "cascade" of contract designs because the reseller is not only a contract follower (for the manufacturer) but also a contract designer (for the salesperson).…”
Section: This Results In the Well-documented Double Marginalizationmentioning
confidence: 99%